From emergency to structure: ways to fight Covid-19 via international cooperation in health from Brazil - Ademar Pozzatti; Luiza Witzel Farias (Revista Brasileira de Política Internacional, 2022)
Abstract This article argues the need for complementarity between emergency and structuring international cooperation in scenarios of health crises in developing countries. Through a review of contemporary literature and document analysis, it analyzes some aspects of the performance of global and Latin American institutions in the Covid-19 pandemic in light of this argument. It also makes a brief survey of forms of international cooperation that emerge from Brazil, with BRICS and Latin American partners, to fight the pandemic, which have a local and sectoral character: paradiplomacy, structuring networks and the role of local agents and health experts.